CHARACTERIZATION ZSM-5 MEMBRANE BASED ON VARIATION OF GAUZE BY TREATMENT SOAKED WITH NITRIC ACID AND ACETONE TO DECREASE CO ONCENTRATION - Ana Hidayati Mukaromah; Tulus Ariyadi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
CO gas is a very toxic gas, because the ability of hemoglobin to bind CO gas to COHb is greater (300 times)  than oxygen, causing the blood to lack of oxygen supply, which can in some cases lead to death.  Therefore, it is necessary to decrease CO gas such as ZSM-5 zeolite membrane. This study aims to determine the growth of ZSM-5 zeolite on surface gauze surface steel. The problem is whether the immersion treatment in 1% nitric acid solution at 333K then continued to be soaked in acetone on the variation of gauze type and stainless steel sizehas effect to sticking precursor ZSM-5 to synthesis ZSM-5 membrane on the low temperature. The resulting membranes were characterized by XRD, FTIR, and SEM-EDX and the ZSM-5 membrane was applied todecrease CO gas concentration in the room. Results showed that the percentage of CO levels based on variation of gauze types (304 and AISI 316) and sizes (100, 200 dan 400 mesh) soaked treated with 1%  nitric acid and and acetone at 363 K was 15.07 ± 1.05 %. The most significant was the highest decrease of CO gas aobserved on Stainless Steel gauze of AISI 316 type. One way anova analysis showed that there was influence of treatment given in the syntesis process of zeolite ZSM-5 membrane by coating to the decrease levels of CO gas and adsorption capacity of zeolit ZSM-5 membrane obtained.Keywords: Gas CO, Zeolit ZSM-5 Membrane, Variation gauze of stainless steel, Treatment was soaking in nitricacid and aceton